IMPROVING FEEDBACK PROCESS FROM FINAL PRODUCT INSPECTIONS FOR CREATING CONTINUOUS IMPROVEMENT - Pouttu, Eino-Juhani Jalmari (My University, 2019)
Quality has costs, but bad quality is even more expensive. This is one of the reasons why improving quality via total quality management has become an essential part for manufacturing organizations globally. One of the most important subareas of total quality management is continuous improvement, which aims to continually correcting operations in a way, that it would create more value to the customer with smaller resources. This thesis is a case study to improve the feedback process from final product inspections commissioned by ABB Motors & Generators Vaasa. The thesis has been constructed with design science research -methodology. The aim of the thesis is to discover methods to improve the feedback process from the final product inspections and ultimately decrease the reclamation rates by applying recommended actions to the final inspection feedback process. Connections between improvements in feedback process and continuous improvement are investigated in this study. The research problem is How to improve feedback process from final product inspections and how to utilize the improved feedback the best way for creating continuous improvement? The results of this thesis indicate, that the feedback from final product inspections is considered highly important in the case organization. During the research, there were five improvement ideas to the feedback process found, which are quite easy to implement. It is challenging to say, whether the improvement ideas have an impact to the reclamation rates, but they were recognized as those practices, which should make the feedback loop more efficient in the future.

Laatu maksaa, mutta huono laatu maksaa vielä enemmän. Tämä on yksi niistä syistä, miksi laadun parantaminen kokonaisvaltaisen laatujohtamisen avulla on kehkeytynyt välttämättömäksi osaksi teollisissa organisaatioissa maailmanlaajuisesti. Eräs tärkeä kokonaisvaltaisen laatujohtamisen aihe on jatkuva parantaminen, joka tähtää jatkuvasti korjaamaan toimenpiteitä siten, että sillä luodaan asiakkaalle lisää arvoa vähemmillä resursseilla. Tämä työ on tapaustutkimus tuotteiden lopputarkastusten palauteprosessin kehittämiseen ja toimeksiantaja on ABB Motors & Generators Vaasa. Työ on rakennettu käyttäen design science -tutkimusmenetelmää. Työn tavoitteena on löytää keinoja parantaa palauteprosessia tuotteiden lopputarkastuksista ja lopulta vähentää reklamaatioiden määrää soveltamalla suositeltuja toimia lopputarkastusten palauteprosessiin. Yhteyksiä jatkuvan parantamisen ja palauteprosessin kehittämisen välillä on tutkittu tässä työssä ja tutkimusongelma on Miten parantaa tuotteiden lopputarkastusten palauteprosessia ja kuinka hyödyntää parannettua palauteprosessia parhaalla mahdollisella tavalla jatkuvan parantamisen luomiseksi. Tutkimuksen tulokset osoittavat, että kohdeorganisaatiossa palautetta pidetään erittäin tärkeänä. Tutkimuksen aikana tunnistettiin viisi melko helposti jalkautettavaa kehitysideaa palauteprosessiin. On haasteellista sanoa, onko kehitysideoilla vaikutusta reklamaatioiden määrään, mutta ne tunnistettiin sellaisiksi toimintatavoiksi, joiden pitäisi tehdä palauteluuppi tehokkaampi tulevaisuudessa.
Keywords: Total Quality Management; Feedback process; Continuous improvement; fi=Tuotantotalous (KTK)|en=Industrial Management|; Master's Programme in Industrial Management